A fixação do marco temporal de ocupação de terras indígenas no Brasil à luz do princípio da primazia da norma mais favorável - Pereira, Rodrigo Clemente de Brito (2017)
In Raposa Serra do Sol Case, the STF has established the thesis that the indigenous communities only have the rights of the lands they traditionally occupy, if such occupation could be verified on the date of the promulgation of the Constitution of 1988. This work aims to verify whether this unique time frame for the identification and demarcation of indigenous lands resists to a test of application of the principle of primacy of the most favorable norm. This principle is provided for in various human rights treaties, can be drawn from the constitutional principle of the prevalence of human rights and is applied in international and domestic jurisprudence. It establishes that law interpreters must, among plurality of normative documents and interpretations on them, seek the solution that guarantees the highest degree of protection of the human being in the concrete case, thus prohibiting the decrease of a standard of protection already achieved in the international or domestic plan. The analysis of the problem starts from the premise that the identification of the most favorable norm is a process of normative concretion that, in general, has to consider the principle of proportionality as well as other guidelines such as the international interpreters understanding, the countermajoritarian function of human rights and the principles of maximum effectiveness and prohibition of retrocession. In this sense, we will examine the issue considering each of these approaches, exploring the jurisprudence of the Inter-American Court of Human Rights, based on the precedents in which it applied the pro persona principle and in which it dealt with indigenous land issues. Finally, we will assess the implications of applying the principle of primacy of the most favorable norm in the interaction between domestic law and the IHRL, in order to demonstrate that, if the establishment of a specific time frame for the characterization of indigenous lands does not resist to a test of application of such principle, it becomes possible and necessary a constitutional mutation on the subject.